Пелагические Ostracoda из субтропического района южной Атлантики - Драпун, И.Е. (Вестник зоологии, 1982)
25 Ostracod species were found ni plankton samples collectedin the South Atlantic subtropical circulation NE section by ine research shio "Mikhail Lomonosoy". Four Conchoecia species (C. curta, C. teretivaluata, C.microprocera and C. procera) appear to be most abundant, population age structure of these species is described. For each or 2 species the data on sample localization and body size characteristic are given in tabular form.